2020
DOI: 10.1038/s41598-020-58761-6
|View full text |Cite
|
Sign up to set email alerts
|

Surgical necrotizing enterocolitis but not spontaneous intestinal perforation is associated with adverse neurological outcome at school age

Abstract: the German neonatal network (Gnn) † Gastrointestinal complications during the neonatal period, i.e. necrotizing enterocolitis (nec) and spontaneous intestinal perforation (Sip), are associated with adverse short-term outcome in very-lowbirthweight infants (VLBWi, <1500 g birth weight). However, little is known about the neurological outcome of survivors at school age. We analysed data of 2241 infants followed-up at the age of 6 years. To determine the effect of NEC and SIP on cognitive outcome in consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 38 publications
(32 reference statements)
2
19
0
1
Order By: Relevance
“…The complex gut-CNS interplay via neural, endocrine, metabolic, and immune factors is referred to as the "gut-brain axis," but the pathways remain to be fully elucidated. However, several diseases of the gastrointestinal tract with inflammatory characteristics impact neurodevelopment and behavioral outcome [23,135]. In preterm infants, NEC is a good example for the potential clinical relevance of a "gut-brain axis."…”
Section: Inflammation and The Preterm Brainmentioning
confidence: 99%
See 2 more Smart Citations
“…The complex gut-CNS interplay via neural, endocrine, metabolic, and immune factors is referred to as the "gut-brain axis," but the pathways remain to be fully elucidated. However, several diseases of the gastrointestinal tract with inflammatory characteristics impact neurodevelopment and behavioral outcome [23,135]. In preterm infants, NEC is a good example for the potential clinical relevance of a "gut-brain axis."…”
Section: Inflammation and The Preterm Brainmentioning
confidence: 99%
“…A multifactorial pathogenesis with immune response to non-physiologic intestinal microbiota ("dysbiosis"), immature intestinal anatomy, and increased expression of pro-inflammatory mediators is involved in the pathogenesis. Several studies have shown significant higher incidences of neurodevelopmental dysfunction [23,[136][137][138][139][140], and brain injury in magnetic resonance imaging [141], especially when infants were longer exposed to the inflammatory process [139,140]. Given the major instability of the microbiome in the first months of life (Fig.…”
Section: Inflammation and The Preterm Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…Parenteral nutrition usually increases the risk of metabolic abnormalities and liver injury, while prolonged exposure to antibiotics will lead to microbiota imbalance, drug resistance, and secondary infection [ 18 , 19 ]. Although surgical intervention in NEC could control enteric content spillage and remove necrotic intestine, severe complications like intestinal stenosis and short bowel syndrome commonly develop [ 20 ]. More importantly, neurodevelopmental delay occurs in a considerable proportion of NEC survivors, especially in infants that underwent surgical intervention [ 21 ]; meanwhile, no targeted treatment for neurological impairment has been recommended currently.…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous factors such as brain immaturity and dysregulated immune responses leading to inflammation-mediated morbidity play a crucial role [3]. Environmental factors such as intensive care, stress, maternal separation, nutritional deficits, circadian rhythm disruption, antibiotics and steroids have also been associated with altered brain development and may therefore contribute to the risk profile of VLBW children [2][3][4][5][6][7]. All these factors have an impact on fragile immune-microbiome co-establishment in preterm children, which occurs in timely association with central nervous system (CNS) development.…”
Section: Introductionmentioning
confidence: 99%